Climate Change and Its Impact on Ecological Succession in Lake Trouna, Southern Libya - Ambark Mustafa; Fatima Sheba; Abdulraof Masoud (AlQalam Journal of Medical and Applied Sciences, 2025)
Lake Trouna reflects successive environmental changes that have occurred in the Libyan Sahara over thousands of years, making it a unique model for studying climate change and ecological succession. Monitoring these changes is therefore essential to understanding the impact of climate variability on aquatic ecosystems and ensuring their sustainability. The ecosystem of Lake Trouna exhibits distinct chemical, physical, and biological characteristics and undergoes significant transformations due to both environmental and anthropogenic factors, affecting its water body, vegetation cover, and surrounding land. These influences contribute to the acceleration of ecological succession. water properties of the lake indicate very high electrical conductivity, reflecting its elevated salinity due to the high concentration of total dissolved solids (TDS). This condition is accompanied by increased levels of nutrients, such as nitrates and phosphates, which contribute to eutrophication and accelerate ecological succession. The high concentrations of sodium and potassium in the fringe soil suggest that the lake water contains these elements, originating from the geological composition of the underlying rocks. This mineral composition influences the life cycles and survival of aquatic organisms. Moreover, the soils surrounding the lake, particularly within the vegetated areas, exhibit a relatively high organic matter content, especially in regions with dense plant cover. This factor plays a supportive role in facilitating ecological succession by creating favorable conditions for its progression.